DETERMINATION OF REPLACEMENT EFFICIENCY OF TRANSFORMERS WITH LONG SERVICE LIFE - M. I. Fursanov; N. S. Petrashevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2014)
The paper shows non-efficient application of the existing economical models for determination of replacement time for transformers with long service life because these models do not take into account real changes in transformer parameters during its operational period. An improved mathematical model for estimation of replacement efficiency of power transformers which are used at substations of power distribution networks has been developed in the paper. The model makes it possible to determine an optimum replacement time and economically justified operational service life of the transformers.